2022
DOI: 10.3389/fcvm.2022.963957
|View full text |Cite
|
Sign up to set email alerts
|

High-normal liver enzyme levels in early pregnancy predispose the risk of gestational hypertension and preeclampsia: A prospective cohort study

Abstract: BackgroundGestational hypertension (GH) and preeclampsia (PE) are severe adverse gestational complications. Previous studies supported potential link between elevated liver enzyme levels and GH and PE. However, given the transient physiological reduction of liver enzyme levels in pregnancy, little is known whether the associations of the high-normal liver enzyme levels in early pregnancy with GH and PE exist in pregnant women.MethodsPregnant women in this study came from a sub-cohort of Shanghai Preconception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…National data with more than 18 million samples from the US showed that the temporal trends in non-alcoholic fatty liver disease (NAFLD) in pregnant women, a most common cause of chronic liver dysfunction, has nearly tripled in the last decade, and reported the tight associations between liver dysfunction and hypertensive complications, postpartum hemorrhage and preterm birth 9 . Our previous studies have reported the signi cant positive associations between maternal abnormal liver function with gestational diabetes mellitus 10,11 . Liver function is usually characterized by the liver function biomarker levels (LFBs), which are routinely measured at the rst antenatal visit in obstetrics and gynecology hospitals, including γ-glutamyl transferase (GGT), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and aspartate aminotransferase (AST) 12 .…”
Section: Introductionmentioning
confidence: 93%
“…National data with more than 18 million samples from the US showed that the temporal trends in non-alcoholic fatty liver disease (NAFLD) in pregnant women, a most common cause of chronic liver dysfunction, has nearly tripled in the last decade, and reported the tight associations between liver dysfunction and hypertensive complications, postpartum hemorrhage and preterm birth 9 . Our previous studies have reported the signi cant positive associations between maternal abnormal liver function with gestational diabetes mellitus 10,11 . Liver function is usually characterized by the liver function biomarker levels (LFBs), which are routinely measured at the rst antenatal visit in obstetrics and gynecology hospitals, including γ-glutamyl transferase (GGT), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and aspartate aminotransferase (AST) 12 .…”
Section: Introductionmentioning
confidence: 93%
“…Finally, some studies have suggested that elevated LFTs in early pregnancy can predict the future development of PE and HELLP [ 77 , 78 , 79 ]; still, most of these studies do not distinguish between pre-term/early PE and term/late PE. It seems that this association is independent of other confounders such as age, body mass index, or the presence of diabetes.…”
Section: Pregnancy-related Liver Disordersmentioning
confidence: 99%
“…The true incidence of elevated LFTs during pregnancy is very difficult to establish because these tests are not routinely performed in all pregnant women and there is substantial heterogeneity among laboratories and centers regarding the definition of “normal” values of liver enzymes. However, some studies have shown that the prevalence of elevated LFTs is up to 5–13% [ 5 , 77 , 79 , 85 ], which is much higher than the canonic 3% prevalence of pregnancy-related liver disease [ 86 ], suggesting that there may be more to it than what was previously thought. Most studies have evaluated LFTs during the first trimester [ 77 , 85 , 87 , 88 ], showing that higher ALT levels are associated with an increased risk of future gestational diabetes [ 77 , 87 , 88 ], large-for-gestational-age babies [ 85 , 89 , 90 ], and pre-eclampsia [ 77 , 78 , 79 ].…”
Section: Other Causes Of Elevated Liver Enzymes: Hypotheses and Specu...mentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Con relación a TGO y TGP no había diferencias estadísticas entre las pacientes normotensas y preeclámpticas y entre las pacientes preeclámpticas con signos de gravedad y sin signos de gravedad, ya que estas enzimas son indicadores de disfunción hepática y ya se sabe en la literatura que el hígado es uno de los órganos afectados por preeclampsia. (33) También observaron en este estudio retrospectivo anomalías de AST y/o ALT en la mitad de los pacientes, la mayoría de ellos tenían ligeras elevaciones de las enzimas hepáticas hasta cinco veces el límite superior normal, pero el 12 % mostró fluctuaciones moderadas a severas de AST y/o ALT. (34) Recuento plaquetario y LDH en las pacientes normotensas y preeclámpticas se obtuvo una p. que es estadísticamente significativa como se esperaba encontrar más disminuidas las plaquetas y las LDH incrementadas que es parte de las complicaciones maternas en la preeclampsia (11) los valores de creatinina en pacientes normotensas y preeclámpticas al igual que en las mujeres preeclámpticas con y sin signos de severidad no hubo una p estadísticamente significativa lo que nos indica que no hubo complicaciones renales.…”
Section: Discussionunclassified